Case report: special imaging features in a uremic patient with intracranial infection caused by Ralstonia mannitolilytica, almost misdiagnosed as demyelinating disease - Kong, Hanxin; Ying, Hao; Yang, Jianhong (Frontiers in Medicine, 2025)
Ralstonia mannitolilytica is a very rare pathogen that causes intracranial infection. It is commonly found in immunocompromised patients and is resistant to multiple antibiotics. In this case report, we present a case of human central nervous system infection caused by Ralstonia mannitolilytica, which was initially misdiagnosed as demyelinating disease due to the specific imaging findings. This case had concurrent uremia and a good response to meropenem under continuous peritoneal dialysis. The diagnosis is mainly based on cerebrospinal fluid analysis and targeted genetic testing by next generation sequencing (NGS). However, the patient had a poor prognosis due to uncontrollable gastrointestinal bleeding and related complications during long-term bed rest. We hope that this case will attract more attention and provide relevant reference for the diagnosis and treatment of other similar patients.